Teacher Perceptions About Student Ethical Decadence (Case Study of Students at Middle School Diponegoro 1 After the Covid-19 Pandemic) - Zila Finola Puspita; Desy Safitri; Sujarwo (Indonesian Journal of Contemporary Multidisciplinary Research, 2023)
This study aims to describe the Decadence of Learners after the implementation of Distance Learning (PJJ) due to the Covid-19 pandemic. The research method used is descriptive with the subject of Student Research. Data were collected using questionnaires, interviews, observation, and literature study. The results of the study show that the teacher's view of student ethical decadence is true, when PJJ teachers only provide core material and rarely provide advice on ethics, lack of parental supervision, some of these things are exacerbated by the existence of social media which students always access without supervision which makes ethical decadence occur